Vascular plants near the margins of their range in Cedarburg Bog. Part II. Dicots - (:unkn) unknown (My University, 1982)
There are two species of gymnosperms and 18 monocots that are near the southern edge of their geographic range in Cedarburg Bog (Reinartz and Reinartz 1981). Six of these may actually reach their range boundary in the bog. Nine species of the Cyperaceae and seven Orchidaceae comprise the bulk of the monocot species that are near their southern limits. The purpose of this paper is to provide an annotated listing of dicot species which have geographically marginal populations in Cedarburg Bog.
Keywords: dicots; Cedarburg Bog; range limits; marginal populations